Pengembangan Bahan Ajar (BMK) dengan Model Metode Qiro’ah - Abdul Muis (Jurnal Pendidikan Islam Indonesia, 2016)
This study focused on how the effectiveness of instructional materials with a model of Islamic education Qiro'ah? Naturally answer this problem requires a fun learning so that students can read books well and learn continuously to obtain the expected results. Students will not be able to learn seriously as long as there is no motivation provided by the teacher to the student, so too are apparently not enough intelligence of a science teacher who has qualified without having pembejaran models that support. One of them is the spirit of learning that encourages the spirit of the students to read the book well in learning is a model Qira'ati.